Українська православна церква та протестантські союзи на Сумщині у 1986-1991 pp. - Філатов, Б. С. (Видавництво НДУ ім.М. В. Гоголя, 2017)
У статті здійснено системний аналіз динаміки розвитку відносин влади з Українською православною церквою і протестантськими організаціями (АСД, ЄХБ, ХВЄ) на Сумщині в роки Перебудови
The article system analysis of development dynamics of authority relationships with the Ukrainian Orthodox Church and protestant organizations (Seventh-Day Adventists, evangelical Baptists, Christians of Evangelical Faith) in Sumy oblast in the years of Perestroika has been made.
Keywords: Українська православна церква; Євангеліські хрис- тиян-баптисти; Адвентисти сьомого дня; Ukrainian Orthodox Church; Seventh-Day Adventists; Baptists, Christians of Evangelical Faith